2015
DOI: 10.1182/blood-2014-08-592733
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the F5 gene (factor V Amsterdam) associated with bleeding independent of factor V procoagulant function

Abstract: Key Points• A novel gain-of-function mutation in factor V leading to increased levels of TFPI and bleeding was identified by whole exome sequencing.• Factor V Amsterdam (F5 C2588G) resembles the mutation (F5 A2350G) leading to East Texas bleeding disorder.We investigated a small Dutch family with a bleeding diathesis, prolonged prothrombin, and activated partial thromboplastin times, in whom no classifying diagnosis was made. The 2 affected relatives had severely decreased in vitro thrombin generation, and lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 5 publications
6
100
0
Order By: Relevance
“…Multiple lines of evidence support this assertion: (1) in vitro studies have shown that the TFPIα basic C-terminus binds to forms of FVa containing the acidic region with high affinity ( K d , ~90 pM) but does not bind to forms of FVa lacking the acidic region 12,15 ; (2) 2 FV mutations producing a truncated B-domain that lacks the basic region but retains the acidic region have been identified 16,35 ; these forms of FV circulate bound to TFPIα; and (3) plasma concentrations of TFPIα (~1 nM) do not inhibit thrombin generation by prothrombinase when the TFPIα basic region or the FVa acidic region is absent. 12 In addition, there is evidence suggesting the TFPIα basic region may bind FVa outside of the B-domain acidic region.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence support this assertion: (1) in vitro studies have shown that the TFPIα basic C-terminus binds to forms of FVa containing the acidic region with high affinity ( K d , ~90 pM) but does not bind to forms of FVa lacking the acidic region 12,15 ; (2) 2 FV mutations producing a truncated B-domain that lacks the basic region but retains the acidic region have been identified 16,35 ; these forms of FV circulate bound to TFPIα; and (3) plasma concentrations of TFPIα (~1 nM) do not inhibit thrombin generation by prothrombinase when the TFPIα basic region or the FVa acidic region is absent. 12 In addition, there is evidence suggesting the TFPIα basic region may bind FVa outside of the B-domain acidic region.…”
Section: Discussionmentioning
confidence: 99%
“…4547 FV-deficient patients also have TFPIα deficiency, and immunodepletion of FV from plasma also removes TFPIα. 46 Moreover, two FV mutants have been identified that bind to TFPIα and cause its concentration to increase 10- to 20-fold.…”
Section: Discussionmentioning
confidence: 99%
“…46 Moreover, two FV mutants have been identified that bind to TFPIα and cause its concentration to increase 10- to 20-fold. 45,47 These two mutations suggest the importance of prothrombinase inhibition by TFPIα, as they are associated with a moderately severe bleeding phenotype. Importantly, however, the FVL patients had normal total TFPI and TFPIα plasma concentrations, indicating the reduced anticoagulant activity of TFPI in FVL plasma was not caused by reduced TFPI concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Patients producing the East Texas and Amsterdam variants of fV, 3,4 both of which tightly associate with plasma TFPIα, highlight the clinical importance of TFPI. These patients have 10-to 20-fold increased plasma TFPIα, an amount sufficient to cause a moderate bleeding diathesis.…”
Section: | Introductionmentioning
confidence: 99%